Hubungan antara Indeks Massa Tubuh dan Frailty terhadap Activities of Daily Living pada Lanjut Usia di Panti Jompo - Zuhal Darwis; Imran Safei (Indonesian Journal of Physical Medicine & Rehabilitation, 2022)
Introduction: High Body Mass Index (BMI) is associated with mortality and morbidity in the elderly. High BMI is also associated with limited physical function. Another issue faced by the elderly is frailty, frailty is associated with decreased exercise capacity, reduced muscle strength, and decreased bone mass leading to adverse health outcomes such as disability, falls, hospitalization and death. Physical frailty is highly prevalent for the elderly who is living in nursing homes. The aim of this study is to determine the association between body mass index and frailty to Activities of Daily Living (ADL) among the elderly in the nursing home. Methods: This study was conducted in 3 nursing homes in South Sulawesi. BMI and frailty were measured. Frailty was assessed by Edmonton Frail Scale (EFS), while activities of daily living was examined by Barthel Index (BI) Results: There were 30 participants, consisting of males 10 (33.3%), and females 20 (66.7%) with a median age of 72 years old, included in this study. The median BMI result was 20.4 (13.3-29.2). The median result of EFS was 5.5 (2-12). The median BI result was 92.5 (45-100). BMI have insignificant correlation with ADL (r = 0.196; p = 0.298), frailty have negative strong correlation with ADL (r = -0.738; p=0.000). Conclusion: There was no significant correlation between BMI and ADL. Otherwise, frailty and ADL have a strong correlation among the elderly in the nursing home.